Masterji’s Resistance in Aravind Adiga’s Last Man in Tower: An Embodiment of the Struggle of the Marginalized Class - Badiuzzaman Shaikh, (The Creative Launcher, 2021)
Aravind Adiga’s Last Man in Tower, published in 2011, is a trenchant critique on the effects of globalization, urbanization, privatization and capitalism in the post-colonial era in India. All these changes in the contemporary society have effectively bifurcated the entire country into two groups—the rich and the poor, the centre and the margin, the privileged upper class and the underprivileged lower class. In the novel Dharmen Shah, a real estate mogul represents the first group of people who are socio-politically and economically highly influential, whereas Yogesh A. Murthy, aka Masterji, is the embodiment of the marginalized class that are constantly dominated and exploited by the former group. My present paper aims to analyse in detail how far Masterji is able to resist the scabrous sufferings unleashed by the rich realtor Dharmen Shah, and how far Masterji’s resistance becomes an incarnation of the resilience of marginalized people in the contemporary society.